(untitled) (Eurasian Scientific Herald, 2022)
This article discusses the mechanism that developed by the authors for the interaction of technical universities, economic universities with enterprises in the real sector of the economy with the participation of private investors, tax, financial and legislative support from the state on the issue of production and transfer of high technologies and training for innovative activities.